The Pelatihan Menjadi Guru Inovatif, Motivatif dan Menyenangkan - Zetriuslita, Zetriuslita; Anggraini, L M (Community Education Engagement Journal, 2019)
The teacher is a figure who is a role model, both for students and for society in general. Especially for students, teachers must be able to provide innovative learning to their students, also be a motivator in educating their students and becoming a pleasant teacher. As an innovative teacher, it means that a teacher can design learning that is new in nature, not as usually is done, and aims to facilitate students on building their own knowledge in order to process behavior change in a better direction in accordance with the potential and differences that students have. Motivating teacher, meaning a teacher is a motivator for students in learning and a pleasant teacher is a teacher can create learning situations that make students learn with a pleasant atmosphere. Being a teacher that is liked by students is a dream and hope of a teacher. Being a teacher who has good motivation and character is a must. For this reason, there needs to be an effort by the teacher to become an innovative teacher, a teacher who is motivating and pleasant so that the relationship between students and teachers is well established.